Sistem Pakar Identifikasi Hama Tanaman Perkebunan Menggunakan Metode Analytical Hierarchy Process (AHP) - Yusup Anwar Siregar; Selamat Subagio; Wita Ferwati (CSRID (Computer Science Research and Its Development Journal), 2026)
Plantation crops such as oil palm, rubber, tea, and coffee are susceptible to pest attacks that can reduce crop productivity. The process of pest identification in the field often encounters obstacles due to limited experts and response time. This study aims to build an expert system based on the Analytical Hierarchy Process (AHP) method to help identify pests based on symptoms and severity of attacks. The AHP method is used to form a decision hierarchy, compile a pairwise comparison matrix, calculate priority weights, and conduct consistency tests. Alternative pests described include planthoppers, stem borers, leaf rollers, stink bugs, and rats, with categories of light and heavy attack levels. The calculation results show the highest composite value in the light category of 0.50717 and heavy of 0.25065. Validation of 15 test cases shows a system accuracy level of 93.33% compared to experts. Usability testing obtained a learnability value of 92.88%, efficiency of 92%, memorability of 94%, error of 94%, and satisfaction of 88.6%. These results indicate that the system is suitable for use as a tool for early identification of plantation pests.